Animal‐mediated long‐distance dispersals and migrations shaping the intercontinental disjunctions of Celastrus (Celastraceae) among five continents. Issue 6 (7th September 2020) - Zhu, Yi‐Xuan; Lei, Feng‐Wei; Tong, Ling; Mu, Xian‐Yun; Wen, Jun; Zhang, Zhi‐Xiang
Abstract: The mechanisms underlying the origin, evolution, and distributional patterns of organisms are a major focus of biogeography. Vicariance and long‐distance dispersal (LDD) are two important explanations for disjunctive distribution patterns among lineages. In‐depth biogeographic studies of taxa that exhibit wide‐ranging disjunctions can provide valuable information for addressing the relative importance of these biogeographic mechanisms. The genus Celastrus contains ca. 30 species that are disjunctly distributed in five continents of both the Northern and Southern Hemispheres, providing an excellent system for historical biogeographic analyses. Here, we used sequence data from five markers (nuclear external transcribed spacer and internal transcribed spacer, and plastid psbA‐trnH, rpl16, and trnL‐F ) to reconstruct the phylogeny of Celastrus and investigate its phylogenetic relationships with Tripterygium, estimate clade divergence times using the fossil‐calibrated method, and infer its ancestral distribution range. Celastrus and Tripterygium were each supported as monophyletic. The morphology‐based classification systems were not supported by the phylogenetic results. The divergence time between Celastrus and Tripterygium was estimated to be 26.22 Ma (95% highest posterior density: 24.46–28.17 Ma), and the diversification of Celastrus were suggested to be linked to global warming events during the Miocene. Celastrus was suggested to have a tropical Asian origin, and dispersed to Central and South America, North America, Oceania, and Madagascar at different periods, most probably through LDD. Birds may have facilitated transoceanic migrations of Celastrus because of its bicolored fruits, which contain red and fleshy arils. Our results highlight the importance of key morphological innovations and animal‐mediated dispersals for the rapid diversification of plant lineages across vast distributional ranges. Abstract : Biogeographic inferences of Celastrus.